The Influence of the Flipped Classroom Based on the Problem-Based Learning Model on the Material of Reaction Rate on Students' Problem-Solving Abilities - Inviolata, Lusia; Laksono, Endang Widjajanti (FKIP Universitas Lampung, 2025)
Problem-solving ability is one of the skills that must be possessed in the 21st century. Problem-solving ability needs to be possessed by students to overcome problems in everyday life and academically. This study aims to analyze the significant differences in students' problem-solving ability on the reaction rate material between students who use flipped classroom learning based on problem-based learning and those who use scientific learning. This type of research is a quasi-experiment with a pretest-posttest control group design. The population in this study was a state high school in West Yogyakarta. The sampling technique used was random sampling of the class. The sample used in this study consisted of two classes, namely the experimental class and the control class. The experimental class used flipped classroom learning based on problem-based learning, while the control class used learning with a scientific approach. Data were obtained through problem-solving ability test instruments in the form of pretests and posttests. The test instruments used were validated theoretically and empirically. Indicators of problem-solving ability measured in the pretest and posttest include understanding the problem, preparing a problem-solving plan, implementing the problem-solving plan, and rechecking the results of the problem-solving. Based on the results of the t-test significance analysis of 0.000 < 0.005, it shows that there is a significant difference in problem-solving ability between students who use flipped classroom learning based on problem-based learning and those who use a scientific approach. Flipped classroom learning based on problem-based learning is one of the innovative learning methods to improve students' problem-solving abilities. Keywords: flipped classroom, problem-based learning, problem-solving ability, reaction rate.